2022
DOI: 10.56093/ijans.v91i12.119822
|View full text |Cite
|
Sign up to set email alerts
|

Aetiologies and therapeutic management of infertility in cows reared in high altitude tribal areas of Himachal Pradesh

Abstract: Infertile cows (664) reared in different tribal areas of Himachal Pradesh were examined thoroughly by rectal examination during infertility treatment camps and diagnosis of reproductive ailments was done to document the prevalence of different types of infertility. The highest prevalence was recorded for anestrus (44.27%) followed by endometritis (42.77%) and miscellaneous reproductive disorders (6.77%). Highest prevalence of anestrus conditions was recorded in Bharmour (51.72%) followed by Kinnaur (49.05%), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Virmani et al (2011) [4] reported that AST were found (U/l) in anestrus (97.83±2.75) cows at 0 day, at the time of AI (128.33±8.01) and after 21 days of AI (127.83±6.06). According to Sharma et al (2022) [34] , in the Himachal Pradesh hills, anestrus cows had an overall concentration of AST of 81.41±3.70 (14.30-155.90) U/L. Chaurasia et al (2016) [35] reported that serum AST values in normal cyclic groups (85.093 U/L), repeat breeder (104.435 U/L), and anestrus (69.124 U/L) were recorded.…”
Section: Ast (U/l)mentioning
confidence: 99%
“…Virmani et al (2011) [4] reported that AST were found (U/l) in anestrus (97.83±2.75) cows at 0 day, at the time of AI (128.33±8.01) and after 21 days of AI (127.83±6.06). According to Sharma et al (2022) [34] , in the Himachal Pradesh hills, anestrus cows had an overall concentration of AST of 81.41±3.70 (14.30-155.90) U/L. Chaurasia et al (2016) [35] reported that serum AST values in normal cyclic groups (85.093 U/L), repeat breeder (104.435 U/L), and anestrus (69.124 U/L) were recorded.…”
Section: Ast (U/l)mentioning
confidence: 99%
“…Embryonic mortality in the reproductively sound animals, is one of the major factors of reproductive failure, decreased fertility, delayed pregnancy in cattle, fewer calves born, reduced milk production and slower genetic progress, especially, in repeat breeder females with late embryonic mortality (Diskin et al 2016). Generally, fertilization rate with artificial insemination (AI) ranges from 85-90 per cent (Sreenan et al 2001;Sharma et al 2019), whereas, conception rate in dairy herds is about 52 per cent (Bansal et al 2019) and declines an additional 10 per cent in lactating dairy cows (W hitlock and Maxwell 2008). Embryos are most susceptible to mortality during their development from morula to blastocyst stage i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of sterility in cows is diseases of reproductive organs [10][11][12][13][14][15][16]. Thus, a careful study on pathomorphism of the reproductive system will allow to objectively defining the nature of this pathology [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%